Emotional responses to climate change information and their effects on policy support - Myers, Teresa A.; Roser-Renouf, Connie; Maibach, Edward (Frontiers in Climate, 2023)
As emotions are strong predictors of climate policy support, we examined multiple discrete emotions that people experience in reaction to various types of information about climate change: its causes; the scientific consensus; its impacts; and solutions. Specifically, we assessed the relationships between these four types of climate information and five discrete emotions (guilt, anger, hope, fear, and sadness), testing whether the emotions mediate the impacts of the information on support for climate policy. We found that each message, except for the consensus message, increased an emotion, and all of the emotions, except guilt, were positively associated with policy support. Two of the messages had positive indirect effects on policy support: the impacts condition increased sadness, which in turn increased policy support, and the solutions condition increased hope, which increased policy support. However, the solutions messages also reduced every emotion except hope, while the impacts message decreased hope. The causes and consensus messages also reduced policy support by suppressing hope.These findings indicate that climate information influences multiple emotions simultaneously, and that message designers should consider how to develop messages that engage across emotional fronts.